BIOAVAILABILITAS TABLET IBUPROFEN PADA PEMBERIAN BERSAMAAN DENGAN EKSTRAK AIR HERBA PEGAGAN (Centella asiatica (L) Urban) PADA KELINCI JANTAN - Sutanti, Depprelia Wahyu; Wahyuningsih, Iis (Universitas Ahmad Dahlan, 2013)
The tendency to use herbal drug simultaneously with synthetic drug may result inan interaction. Based on research, aqueous extract of Centella asiatica (L) Urbancontains saponin (asiaticoside and madecassoside) compounds that inhibit CYP450and is a safe herbal alternative that is used for anti-inflammatory treatment. The aim ofthis study was to investigate the effect of aqueous extract of Centella asiatica (L) Urbanto the ibuprofen tablet bioavailability in male rabbits. Both compounds are metabolizedby CYP450 enzymes in the same way with different mechanism. The cross over designwith the same subject was used in this study. The samples consisted of 400 mg ibuprofenwith 0%b/v, 25%b/v, 50%b/v dan 100%b/v aqueous extract of Centella asiatica (L)Urban respectively. The blood were taken after 0; 0,5; 1; 1,5; 2; 2,5; 3; 3,5; 4; 6; 8; 10hours after samples treatment, then the ibuprofen plasma concentration weredetermined spectrophotometrically. The results then were used to evaluat thebioavailability parameters: tmaks, Cpmaks, and AUC and were analyzed using ANOVAtest in the same way as well as the 95% trust standart. The results showed, the use ofibuprofen tablet stimultaneously with aqueous extract of Centella asiatica (L) Urbanincreased Cpmaks dan AUC, but there were no influence to the tmaks value. The use ofibuprofen tablet stimultaneously with 50 %b/v and 100 %b/v aqueous extract ofCentella asiatica (L) Urban had a significant influence to the bioavailability ofibuprofen.